The Mechanism of Quality Changes in Grass Carp (Ctenopharyngodon idella) During Vacuum-Assisted Salting Brining with Physicochemical and Microstructural View - Jianrong Ma; Jian Shi; Ruiying Lv; Xin Jiang; Qingqing Jiang; Dajun Wang; Shumin Zhang; Wenzheng Shi (Foods, 2025)
This study investigated the effects of vacuum impregnation (V) and atmospheric pressure impregnation (C) on the quality and microstructure of grass carp (Ctenopharyngodon idella) fillets during a 120 min brining period under 5.8% NaCl (w/v) and 4 °C. Vacuum impregnation significantly enhanced brining efficiency, achieving higher salt content (2.01%) and accelerated mass transfer kinetics, as evidenced by Peleg model parameters. Both treatments improved the water-holding capacity (WHC), increasing from 80.16% to 91.47% (C) and 89.92% (V), while reducing free water proportion. A microstructural analysis revealed a reduction in extracellular space in fillets, which further affected the fillet WHC and texture. Vacuum brining also mitigated lipid oxidation, yielding lower thiobarbituric acid-reactive substances (TBARSs: 0.237 mg MDA/kg). Texture analysis indicated reduced hardness and increased springiness/cohesiveness in fillets. Despite a slight decrease in lightness, vacuum-assisted brining preserved sensory quality and aligned with low-salt dietary trends. These findings underscore vacuum technology’s potential to optimize brining efficiency and product quality in industrial applications.